Harmonizing Modern and Indigenous Democracy: An Exploration of Traditional Democratic Values in Ethnic Communities of Indonesia - Iskandarsyah Siregar (Lakhomi Journal Scientific Journal of Culture, 2023)
The extended journey towards both economic and political modernization within Indonesia's democratic framework has led to a transformation of its society into an industrialized community. However, this change has largely failed to boost the economic prospects of the general populace. Moreover, the turbulent nature of Indonesia's democratic evolution has not aligned well with the principles of open dialogue and inclusive discussion, as advocated by its foundational philosophy, Pancasila. Over the last 15 years, the amalgamation of development-oriented politics and political liberalization has exerted a detrimental impact on the nation's unique cultural identity and wisdom. The upcoming research aims to revisit and revitalize the indigenous political ideologies and social values held by various ethnic groups and community structures in Indonesia. The objective is to shed light on the unexplored potential of social capital to enhance the quality of the country's democratic governance. The research will focus on two main categories for its case study: Firstly, it will delve into ethnic groups, concentrating specifically on the Wajo and Minang communities; Secondly, it will study communities that are active in a number of urban parks across the Java region. The study is rooted in the theoretical framework of consultative democracy and will utilize qualitative research methods interpreted through the lens of political anthropology to obtain nuanced, context-rich insights.